Immune microenvironment regulation and clinical immunotherapy strategies of metastatic liver cancer - Liu, Dan; Li, Mingzhu; Liang, Ying; Xu, Fang; Li, Runtian; Sun, Yang (Frontiers in Immunology, 2025)
Metastatic liver cancer (MLC) remains a leading cause of cancer-related mortality due to the liver’s unique immunotolerant microenvironment and high vascularization. Key mechanisms involve KC-mediated fibronectin deposition, neutrophil extracellular traps (NETs), and MDSC-driven T-cell exhaustion. Clinically, therapeutic strategies targeting the tumor microenvironment (TME) such as CSF1R inhibition, CCR2/CCR5 blockade, and CD40 agonism show promise in preclinical and early-phase trials, especially when combined with immunotherapy. However, challenges remain in overcoming systemic immunosuppression. This review summarizes the dual roles of hepatic immune cells including Kupffer cells (KCs), neutrophils, and myeloid-derived suppressor cells (MDSCs) in either suppressing or promoting metastatic colonization. We elucidate how the liver’s immunological balance, governed by innate and adaptive responses, shifts toward immunosuppression during metastasis, fostering a pro-tumor niche. This synthesis of immunological insights underscores the potential of TME-modulating therapies to improve outcomes in MLC.